What contribution can design research make to fostering innovation transfer processes in German VET? - Peitz, Nina-Madeleine [Verfasser]; Ertl, Hubert [Verfasser] (My University, 2025)
“Theoretical findings indicate that the transfer of knowledge between research and practice should become a research object in itself, supported in the form of overarching “metaprojects”. The project “Accompanying Research InnoVET” represents such an undertaking and develops, tests, and evaluates support mechanisms that aim at improving translational processes between research and practice in the innovation transfer within the nationwide German InnoVET programme. In this context, this contribution examines the features that contribute to the success of a research-practice dialogue. It addresses the question which contribution design-based research (DBR) can make to (the transfer of) innovations developed in the InnoVET programme. Systematic results are based on literature analysis, a survey of programme participants and development talks with practitioners and researchers. Results emphasize, e.g., the significant role the interaction between research and practice plays, the importance of actors’ transfer-oriented mindset and furthermore, the need for exchange formats. The results demonstrate the contribution DBR can make to improve innovation transfer in large-scale programmes thereby generating new theories for transfer strategy measures.“ (authors‘ abstract; BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; 370; InnoVET; Innovationsforschung; Wissenstransfer; Wissenschaftliche Begleitung; Praxisbezug; Gestaltungsbasierte Forschung; Literaturanalyse